The costs of offering HPV-testing on self-taken samples to non-attendees of cervical screening in Finland - Virtanen, Anni (BMC Womens Health, 2015)
BACKGROUND: Offering self-sampling to non-attendees of cervical screening increases screening attendance. METHODS: We used observations from two Finnish studies on the use of self-sampling among the non-attendees to estimate in a hypothetical screening population of 100,000 women the possible costs per extra screened woman and costs per extra detected and treated CIN2+ with three intervention strategies; 1) a primary invitation and a reminder letter, 2) a primary invitation and a mailed self-sampling kit and 3) two invitation letters and a self-sampling kit. The program costs were derived from actual performance and costs in the original studies and a national estimate on management costs of HPV related diseases. RESULTS: The price per extra participant and price per detected and treated CIN2+ lesion was lower with a reminder letter than by self-sampling as a first reminder. When self-sampling was used as a second reminder with a low sampler price and a triage Pap-smear as a follow-up test for HPV-positive women instead of direct colposcopy referral, the eradication of a CIN2+ lesion by self-sampling was not more expensive than in routine screening, and the addition of two reminders to the invitation protocol did not increase the price of an treated CIN2+ lesion in the entire screened population. CONCLUSIONS: As a first reminder, a reminder letter is most likely a better choice. As second reminder, the higher costs of self-sampling might be compensated by the higher prevalence of CIN2+ in the originally non-attending population.